Touch : sensuous theory and multisensory media - Marks, Laura U., 1963- (University of Minnesota Press, 2002)
In Touch, Laura U. Marks develops a critical approach more tactile than visual, an intensely physical and sensuous engagement with works of media art that enriches our understanding and experience of these works and of art itself.